(untitled) (Pyrmont, N.S.W., 2008)
These amandments includes : reducing the regulatory burden on provides of financial services; simplifying company reporting obligations; improving auditor independence rules; removing unnecessary member approval requirements in relation to small transactions; facitlitating funddraisings
Keywords: Corporation law,Luật doanh nghiệp; Australia,Úc